Retracted: Data exploration of college students' humanistic literacy in the internet age under the big data environment - Taixiang Tang; Huihua Zhang (IET Software)
Abstract Retraction: [Taixiang Tang, Huihua Zhang, Data exploration of college students' humanistic literacy in the internet age under the big data environment, IET Software 2023 (https://doi.org/10.1049/sfw2.12087)]. The above article from IET Software, published online on 20 January 2023 in Wiley Online Library (wileyonlinelibrary.com), has been retracted by agreement between the Editor‐in‐Chief, Hana Chockler, the Institution of Engineering and Technology (the IET) and John Wiley and Sons Ltd. This article was published as part of a Guest Edited special issue. Following an investigation, the IET and the journal have determined that the article was not reviewed in line with the journal’s peer review standards and there is evidence that the peer review process of the special issue underwent systematic manipulation. Accordingly, we cannot vouch for the integrity or reliability of the content. As such we have taken the decision to retract the article. The authors have been informed of the decision to retract.